The English speaking anxiety of public health students of STIK Bina Husada Palembang - Agus Wahyudi (Language and Education Journal, 2020)
The learning process is an adaptation method dole out by people to grasp and master the science. During this learning period that the individual adjusts himself to the changes that occur quickly and surely. Speaking publically will cause anxiety as a result of each activity dole out by humans contains a tendency to develop anxiety. Horwitz (2001) expresses that one-third of the scholars who study foreign languages expertise a minimum of at a median level. The subjects were 13 students of the sixth semester who took English for Public Health in the academic year of 2020/2021. The frequency and the English speaking anxiety level became the purpose of this study to be found out. To collect the data English speaking anxiety questionnaire was used. The first questionnaire results showed that 2 students (15%) answered very often, 4 students (30%) often, 6 students (46%) rarely, and 1 student (7%) never felt anxious when speaking English. The second questionnaire showed that 2 students (15%) in high category, 10 students (76%) in medium, and 1 student (7%) in low anxiety. In accordance to the students’ answer, it is hoped that scholars understand that it is natural to form mistake in form